A stratified model for health outcomes in ankylosing spondylitis. Issue 10 (25th July 2011) - Machado, Pedro; Landewé, Robert; Braun, Jürgen; Hermann, Kay-Geert A; Baraliakos, Xenofon; Baker, Daniel; Hsu, Ben; van der Heijde, Désirée
Abstract : Objective: To investigate the relationships between several health outcomes in ankylosing spondylitis (AS). Methods: Baseline pretreatment data from 214 patients with AS participating in the AS Study for the Evaluation of Recombinant Infliximab Therapy were analysed. Measures of health-related quality of life (HRQoL) and physical function were used as dependent variables in linear regression analysis. Associations between HRQoL (36-Item Short Form (SF-36)), physical function, clinical disease activity, spinal mobility, structural damage, MRI inflammation, disease duration, age, gender, body mass index and HLA-B27 were explored. Univariate associations were retested in multivariate models. The robustness of the models was evaluated by sensitivity analyses. Results: The physical component of SF-36 was independently associated with measures of physical function and disease activity (adjusted R 2 (adjR 2 )=0.39–0.40). The mental component of SF-36 was independently associated with physical function (adjR 2 =0.07). Physical function was independently associated with measures of spinal mobility and disease activity (adjR 2 =0.39–0.45). Spinal mobility was hierarchically shown to be an intermediate variable between structural damage and physical function, while physical function was shown to be intermediate between spinal mobility and the physical component of SF-36. Conclusion: According to the proposed stratified model for health outcomes in AS, HRQoL is determined by physical function and disease activity, physical function is determined by spinal mobility and disease activity, and spinal mobility is determined by structural damage and inflammation of the spine. As more is learnt about how to measure AS, knowledge about the disease improves and better decisions can be made on the assessment and treatment of this disease.